(untitled) (International Seven Journal of Multidisciplinary, 2024)
Angled dental implants have emerged as an effective solution in clinical settings where the placement of straight implants is constrained by unfavorable bone positions or the presence of adjacent anatomical structures. The angulation of implants significantly influences stress distribution around the implant, impacting its stability and longevity. Research highlights that the direction of applied loads is critical, as angled implants can generate greater bending and shear forces compared to straight implants, potentially leading to stress concentrations in surrounding bone. Finite element analysis (FEA) is commonly used to model these conditions, offering insights into stress zones and predicting potential failure areas. Bone quality plays a vital role in how implants respond to applied forces, with denser bones effectively dissipating forces while more porous bones are at higher risk of resorption and integration failure. Studies indicate that excessive stresses on angled implants can lead to bone resorption, compromising long-term stability. Therefore, careful consideration of implant angulation, connection type, bone quality, and thorough surgical planning is essential. Recent studies, including those investigating the effects of implant design and bone density on stress distribution, have demonstrated that varying implant threads and angulated abutments affect the stresses experienced by surrounding bone and implants. The findings emphasize the need for appropriate implant selection and a detailed assessment of bone anatomy and patient-specific clinical conditions. By incorporating advanced technologies like FEA, clinicians can enhance their understanding of biomechanical interactions, ultimately leading to improved clinical outcomes and patient satisfaction. Continuous education and the implementation of best practices in dentistry remain vital for the successful application of angled dental implants.